Quality Control of Legano Products Using DMAIC and FTA for Quality Improvement Efforts at PT Fitria Jaya Lestari - Fazliansyah, Muhamad Rohul; Dimas, Akmal; Putra, Muhammad Reza Ramanda; Alfiansyah , Daffa; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
Inadequate quality control at PT Fitria Jaya Lestari has caused problems for the company. This problem is characterized by a fairly high level of defects in Legano products, reaching 11.28%. The problem arises due to the absence of an effective quality control method at PT Fitria Jaya Lestari. To analyze this problem, the DMAIC method is used in conjunction with Fault Tree Analysis (FTA). The purpose of this research is to identify the causes of the high defect rate and provide improvement suggestions to overcome the defect problem in Legano products. The method applied in this research is DMAIC with Fault Tree Analysis to find out the causes of high defect rates and propose improvements for defect problems in Legano products. The results of the analysis show a DPMO value of 28,443.58 or the possibility of 28,443 defects in a 12-month period, with the causes of defects including Humans, namely the lack of job training for employees and the low quality of human resource graduates, Machines, namely temperatures that are too high, Materials, namely raw materials made from rubber waste, and Methods, namely the absence of guidelines for cutting. Given these results, there are several suggestions for improvement such as conducting job training for employees, recruiting workers with good quality graduates, changing raw materials from rubber waste to rubber seeds, and making work instructions and jig parts as cutting guides.